Corporate finance in multinational companies - Zenoff, David B. (London : Euromoney publications, 1986)
This book is intended to extend one step further the exchange of ideas, information, perspectives and wisdom about the financial management of large international companies. The book provides original monographs contributed by leading corporate finance practitioners and advisors.
Includes bibliographical references.
hza 08/08/2018
Loans
Keywords: Corporate finance